A Review on Nanoparticle Filled Polymer Nanocomposites - T, Sridhar; Kini U, Achutha; Hiremath, Anupama (International Journal of Engineering and Technology, 2018)
Nanoparticle filled polymer composites are a new class of engineering materials that are finding widespread applications in numerous fields owing to their tailorable mechanical, thermal and electrical properties that are superior to traditional monolithic materials. But, in order to realize the full potential of such nano composites, one has to ensure proper control over the uniform dispersion of nanoparticles within the polymeric matrices and should understand the interfacial reactions between the chemically distinct filler and the matrix. The present paper reviews the mechanical thermal and electrical properties of nanoparticle filled polymer nanocomposites. An effort is made to understand various fabrication processes employed to fabricate nanoparticle filled polymer nanocomposites.Â Â